2019
DOI: 10.18472/sustdeb.v10n3.2019.24751
|View full text |Cite
|
Sign up to set email alerts
|

Permanent preservation, coverage area and use of the land in the hydrographic basin of the Almas River, microregion de Ceres, Goiás, Brazil

Abstract: The aim of this study was to map the Permanent Preservation Areas (PPAs), as well as land cover and land use in the Almas River basin in Goiás, Brazil, based on geoprocessing. The results showed the remnants of the original vegetation are limited to fragments and occupy 32.52% of the area. Grassland is the dominant use, which is distributed throughout the area. Sugar cane and grains secondarily occupy other areas of the river basin. The mapped permanent preservation areas occupy an area of 1,182.22 km2, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In terms of environment, it is noteworthy mentioning several works that apply remote sensing, such as: 1) that performed by Barbalho et al (2019) with the use of 'Rapideye images' together with geoprocessing techniques; 2) the use of ArcGIS (Geographic Information Systems processing program, GIS) with the use of Google Earth images, as described in Viera et al (2018); 3) research with the application of GIS and temporal analysis of environmental devastation studies, reported in Guistina et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environment, it is noteworthy mentioning several works that apply remote sensing, such as: 1) that performed by Barbalho et al (2019) with the use of 'Rapideye images' together with geoprocessing techniques; 2) the use of ArcGIS (Geographic Information Systems processing program, GIS) with the use of Google Earth images, as described in Viera et al (2018); 3) research with the application of GIS and temporal analysis of environmental devastation studies, reported in Guistina et al (2018).…”
Section: Introductionmentioning
confidence: 99%